MASS-DEPENDENT FRACTIONATION OF MG, SI, AND FE ISOTOPES IN FIVE STONY COSMIC SPHERULES - Alexander C.M.O.; Taylor S.; Delaney J.S.; Ma P.; Herzog G.F. (My University, 2002)
We have measured with an electron microprobe the Mg, Al, Si, Ca, Ti, Mn, and Fe contents of five strongly heated stony cosmic spherules (sCS) from the South Pole water well. We have also measured the isotopic compositions of Si, and when possible of Mg and of Fe in these objects by ion microprobe. Except for iron, the measured elemental compositions are chondritic within a factor of 2. In four samples, the ratio of 57Fe/56Fe exceeds the terrestrial value by 3.5%% to 48%%. Mass-dependent fractionation of the isotopes of Si ranges from ~2 to ~8 %%/AMU in three samples. Mg is clearly fractionated in only one sample, for which δ25Mg = ~8 %%. The extent of mass-dependent fractionation of the isotopes and, by implication, of evaporative loss generally follows a trend Mg < Si < Fe. The trend is similar to that found in laboratory heating experiments of charges with solar composition. Although the observed isotopic inhomogeneities within some samples call into question the strict validity of the Rayleigh equation for the sCS, its approximate application to our new and to previously published results for Mg suggests that evaporative losses of greater than 40 wt.% occur rarely from sCS, and that the precursor grains of the sCS had a CM-carbonaceous-chondrite-like complement of Mg, Si, Ca, and Al. Low Fe contents relative to CM abundances could reflect an unusual precursor composition, or, more probably, losses by processes that did not fractionate isotopes, i.e., ejection of immiscible FeS and FeNi beads from the melt or rapid, complete separation and decomposition of FeS at the surface.